The Role of Biomechanics in Enhancing Athletic Performance - Mahmood , Muhammad Zahid; Khaskheli , Dr. Nisar Ahmed; Noreen , Dr. Zobia (Al-Aijaz Research Journal of Islamic Studies & Humanities, 2025)
Biomechanics has emerged as a cornerstone of modern sports science, providing a precise understanding of how forces, motion, and mechanical principles influence human movement and athletic performance. The present study aimed to examine the role of biomechanics in enhancing athletic performance, preventing injuries, and improving training design across different sports disciplines. A quantitative research design was employed, using a descriptive and analytical approach to explore the relationships between biomechanical applications and performance outcomes. Data were collected from 120 university athletes (70 male, 50 female) through a structured Likert-scale questionnaire assessing perceptions of biomechanics and through biomechanical testing involving wearable sensors, force plates, and motion analysis systems. The instruments were validated through expert review, and internal reliability was confirmed (Cronbach’s α > 0.70). Descriptive statistics, including means, standard deviations, and frequencies, summarized demographic characteristics and survey responses. Inferential analyses correlation, regression, and independent samples t-tests were conducted using SPSS version 27. Results revealed significant positive correlations between biomechanics awareness and key performance indicators such as speed (r = 0.62, p < 0.01), strength (r = 0.59, p < 0.01), and overall performance (r = 0.67, p < 0.01). Regression analysis showed that biomechanics significantly predicted athletic performance (β = 0.54, R² = 0.38, p < 0.001). No significant gender differences were observed (p > 0.05). These findings demonstrate that the application of biomechanical principles and technologies significantly enhances athletic performance, offering valuable implications for training optimization, injury prevention, and the broader integration of evidence-based biomechanics into competitive sports.